Motion-solving for Spatial 3-RPS Parallel Mechanism based on Co-simulating - Dan Bochou; Li Qi; Hou Xiaoli (Jixie chuandong)
On the basis of the analysis of spatial 3-RPS parallel mechanism,the method instruction of the mechanism motion solving and inverse kinematics equation are obtained. For the parallel mechanism,the forward kinematic solution is complex,the kinematic solution of spatial 3-RPS parallel mechanism is achieved by the combining of Pro/E software,MATLAB software and ADAMS software. The 3 D model is established in Pro/E software,and put into ADAMS software to edit and define. Through giving the kinematic position,the rotation angle curves of the rotation joint and the output of the attitude angles are achieved by the MATLAB software. The curves can be used as driving function to the three forearms after editing and conversion with the ADAMS function,then,forward kinematic solution is achieved. The results are identical with the inverse solution,that proved the reliably and correctly of the method. The method can be used in the virtual prototyping technology,because of simple solution process and intuitive kinematic performance.